2015
DOI: 10.1016/j.tcm.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

SK channels and ventricular arrhythmias in heart failure

Abstract: Small-conductance Ca2+-activated K+ (SK) currents are important in the repolarization of normal atrial (but not ventricular) cardiomyocytes. However, recent studies showed that the SK currents are upregulated in failing ventricular cardiomyocytes, along with increased SK channel protein expression and enhanced sensitivity to intracellular Ca2+. The SK channel activation may be either antiarrhythmic or proarrhythmic, depending on the underlying clinical situations. While the SK channel is a new target of antiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…However, in failing ventricles and in normal ventricles with atrioventricular block or hypokalemia, the I KAS are upregulated and became an important repolarization current. 1719 Consistent with the findings reported by Xu et al, 17 we found that apamin prolonged APD significantly in mouse atria. However, the magnitude of prolongation was much larger in Dct −/− than in Dct +/− mice.…”
Section: Discussionsupporting
confidence: 91%
“…However, in failing ventricles and in normal ventricles with atrioventricular block or hypokalemia, the I KAS are upregulated and became an important repolarization current. 1719 Consistent with the findings reported by Xu et al, 17 we found that apamin prolonged APD significantly in mouse atria. However, the magnitude of prolongation was much larger in Dct −/− than in Dct +/− mice.…”
Section: Discussionsupporting
confidence: 91%
“…Apamin, a Western honey bee toxin that specifically inhibits SK channels,3 reduces the slow afterhyperpolarization and depolarizes the membrane potential, resulting in rapid and irregular neuronal firing 4. Subsequent studies showed that both SK channel proteins and apamin‐sensitive SK currents ( I KAS ) are abundantly present in the atria, atrioventricular node, pulmonary vein, and ventricular myocytes (VMs) of different species and play an important role in repolarization and arrhythmogenesis especially in heart failure and myocardial ischemia 5, 6. In both normal and failing ventricles, prolongation of the pacing cycle length (PCL) further increases the importance of I KAS in repolarization 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an excessive amount of I KAS may shorten the action potential duration (APD) and promote recurrent ventricular fibrillation 15. Therefore, I KAS blockade may be either proarrhythmic or antiarrhythmic, depending on the mechanisms of arrhythmia 5. While I KAS may be important in cardiac arrhythmogenesis, whether I KAS is present in the PCs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While selective hERG channel blockers are used for the treatment of atrial fibrillation, the risk of Torsade de Pointes associated with these drugs is well recognized, and all new drugs are now screened for interaction with this channel and risk of ventricular proarrhythmia. In the current issue, Chang and Chen review the evidence for the use of selective calcium-activated potassium channel blockers in the treatment of ventricular arrhythmias (2). …”
mentioning
confidence: 99%
“…Given the diminished repolarization reserve in heart failure, and the intrinsic heterogeneity associated with repolarization and conduction velocity in the failing heart, selective pharmacologic suppression of IKAS is not an obvious choice as a first line therapy. Chang and Chen recognize the significant risk of pro-arrhythmia associated with changes in SK channel expression in the setting of AV block and other conditions (2). Bonilla and colleagues conclude that IKAS blockade for treatment of AF is not warranted in the setting of HF, due to the increased risk of ventricular proarrhythmia (3).…”
mentioning
confidence: 99%